The differences in learning students outcome on the subject respiratory system by using audiovisual media in modern Islamic boarding school Banda Aceh - Ulya Azra; Cut Nurmaliah; Ismul Huda (Jurnal Edubio Tropika, 2018)
This study aimed to determine the differences between the learning outcome of male and female students in the subject respiratory system by using audiovisual media. This study conducted from February 5 to February 28, 2017. The method used in this study was a quasi-experimental method with The Static Group Pretest-Postest Design. The population in this study was the students of class XI from the senior high school of Inshafuddin and Babunnajah consisted of 164 students. While the sample in this study consisted of 118 students, the male class was 54 students, and the female class was 64 students. The instruments used in this study is multiple choice tests to measure student’s learning outcome. The parameter in this research was the result of a student’s learning outcome. Data analysis was performed using the Mann Whitney U test at a significant level of 0,05. Result in Mann Whitney U test on student’s learning outcome showed that Sig. (2-tilled) 0,708 0,05. This study concluded that there were no differences in learning outcome between male and female students on the subject respiratory system by using audiovisual